Mulheres refugiadas e o mercado de trabalho: um estudo no município de São Paulo - Andrade, Marisa (2014)
This thesis aims to present the integration into the labor market and living conditions of refugee women in São Paulo . To achieve this purpose it was necessary to thoroughly investigate the reality of refuge in the world and in Brazil , considering the homeland legislation , international conventions and treaties to which Brazil is subsidiary . Accordingly, we sought to first identify the different groups of people moving in search of refuge , were considered as refugees only those people that according to Law 9474 of July 22, 1997 in art . I were forced to flee their homes in conflict situations , for religious, ethnic , political , among others . Conflicts endanger the life, liberty and security of the population suffering threats and persecutions effective , triggering the refuge . This situation forces the flight of people from their countries in search of a better life in another that receives . But to survive in another country need to work and this triggered the research in question , in which we investigated the inclusion of these women in São Paulo labor market , considering the work category and the changing world of work in the context of the capitalist system , linked intrinsically conditions such inclusion as a determinant for survival and reflect on the living conditions of these women in their educational background , professional qualifications and consequently the mode of insertion in the labor market factor. Accordingly, we proceeded to literature , which supported the theoretical study on the topic . The theoretical appropriation in relation to history and legislation was essential to initiate the study. Through qualitative research , based on critical and analytical examination of reality investigated , we proceeded to the analysis of the object of study , as well as field research by providing information necessary to the description and interpretation of the studied phenomenon . Thus , we proceeded to the examination of this particular reality through the use of standardized techniques for data collection , such as questionnaires and in-depth interview. The contact with four organizations active on the issue of refuge provided the data and conditions for contact with the refugees . We selected a representative sample of 53 refugee women living in the city of São Paulo , which provided information relevant to the analysis developed in this work . In the research process sought to unveil the concept of work , changes in this universe , the world of work and its transformations over the historical process of capitalist society , inter - relating them to the reality of refugee women . In this process , we sought to uncover the life story of refugee women, their living conditions, as it has been given its survival . However , despite having centered his focus of interest regarding the integration into the labor market and living conditions of this social group , this study was not limited solely to describe such conditions , but investigate what the state agency responsible for acceptance and permanence of these people have done and can do to accomplish what is already structured in speech , true hospitality to refugees , in the present study to refugees . As a corollary to this line of argument , we have that without the active presence of the state as a structuring agent , the country will hardly able to guarantee social protection to this group , which , as already mentioned , has grown every day . Considering the aspects sometimes punctuated , it is expected that this work can serve as an additional source of research and interest to all those who have refuge in their area of expertise , especially for those who dedicate themselves to the study of issues related to the rights of refugees , given still seeking to apprehend about living as refugees in São Paulo megalopolis . It is estimated that this research guidance for other researchers in the social service area and that it , unlike become a production on the shelves of academia , creates new discussions and debates in the new area of concern in some and in others , awakening " new looks " toward a more critical social and political refuge and about the reality of refugee